A Decrease in Plasminogen Activator Inhibitor-1 Activity after Successful Percutaneous Transluminal Coronary Angioplasty Is Associated with a Significantly Reduced Risk for Coronary Restenosis - Huber, Kurt; Jörg, Maria; Probst, Peter; Schuster, Ernst; Lang, Irene; Kaindl, Fritz; Binder, Bernd R (Thrombosis and Haemostasis, 1992)
To determine a possible relation of changes in plasma levels of plasminogen activator inhibitor 1 (PAI-1) and tissue plasminogen activator (t-PA) to the development of coronary restenosis after successful coronary angioplasty (PTC A), we followed 104 patients with a low grade residual stenosis after PTCA (less than 30%) for a period of 12 months. PAI-1 plasma levels (functional activity) and t-PA antigen were determined 1 day before PTCA and 3 days, 3 months and 6 months thereafter. Thirty-four patients (32.69%) developed angiographically proven coronary restenosis (group A) within a time range of 4-48 weeks (median 12.5 weeks) after PTCA while the remaining patients (group B) had neither clinical signs nor angiographic evidence of restenosis after 6 months. No significant differences could be demonstrated in t-PA antigen or PAI-1 activity (plasma levels between the two groups of patients the day before PTCA). During the whole observation period t-PA plasma levels were not significantly different between the two groups; however, PAI-1 plasma levels were significantly higher at 3 months and 6 months after PTCA in patients of group A (p <0.005). When the pattern of PAI-1 plasma levels over time (increase or decrease between two consecutive time points of blood collection) was used to discriminate between the two study groups only 3.5-18% of patients with a decrease in PAI-1 developed coronary restenosis within the following observation period in contrast to 25-58% of patients with an increase in PAI-1 plasma levels (p <0.05 to p <0.0005).